Long-term inflammatory pain does not impact exploratory behavior and stress coping strategies in mice. Issue 6 (June 2021) - Burek, Dominika J.; Massaly, Nicolas; Doering, Michelle; Zec, Azra; Gaelen, Jordan; Morón, Jose A.
Abstract : Abstract: Pain puts patients at risk for developing psychiatric conditions such as anxiety and depression. Preclinical mouse models of pain-induced affective behavior vary widely in methodology and results, impairing progress towards improved therapeutics. To systematically investigate the effect of long-term inflammatory pain on exploratory behavior and stress coping strategy, we assessed male C57BL/6J mice in the forced swim test (FST), elevated zero maze, and open field test at 4 and 6 weeks postinjection of Complete Freund's Adjuvant, while controlling for testing order and combination. Inflammatory pain did not induce a passive stress coping strategy in the FST and did not reduce exploratory behavior in the elevated zero maze or the open field test. Using systematic correlational analysis and composite behavioral scores, we found no consistent association among measures for mice with or without inflammatory pain. A meta-analysis of similar studies indicated a modest, significant effect of Complete Freund's Adjuvant on exploratory behavior, but not immobility in the FST, and high heterogeneity among effect sizes in all 3 paradigms. Given the urgency for understanding the mechanisms of pain comorbidities and identifying novel therapies, these findings support the reallocation of our limited resources away from such unreliable assays and toward motivated and naturalistic behaviors. Future studies in pain and psychiatric translational research may benefit by considering outcomes beyond binary categorization, quantifying the associations between multiple measured behaviors, and agnostically identifying subtle yet meaningful patterns in behaviors. Abstract : Supplemental Digital Content is Available in the Text.Systematic behavioral phenotyping and meta-analysis indicate low validity of exploration and stress coping for modeling the pain-induced negative affect and support a refocusing on motivation.